IMPLEMENTASI FUNGSI-FUNGSI MANAJEMEN DALAM MENINGKATKAN MUTU PENDIDIKAN - Sulfiana, A; Azham Mubaraqah, Muh.; Rahim, Rahim; Syamsuriadi, Syamsuriadi (DIDAKTIKA, 2022)
Education is all a learning experience that students get through with all environments and lifelong. To achieve the goals, National Education seeks to improve and update the education system in Indonesia, namely in the form of curriculum renewal, teacher arrangement, increases in education management, as well as the development of education facilities and infrastructure. By this renewal, it is expected to produce creative humans that are in accordance with the demands of the era, which in the end quality of education in Indonesia increased. The quality of education can be interpreted how far away goods and services can provide satisfaction to customers according to or exceed customer expectations. The quality factors referred to are human resources in MA Ar-Raihan Lattekko which includes principals, teachers and students, based on the above factors, the school development is very prioritizing increasing the quality of education teachers, namely increasing school teachers through academic and professional education, develops sustainablely in accordance with the vision and quality of the implementation program at the existing schools. The research method used is qualitative research. The results of this research indicate that MA Ar-Raihan Lattekko has implemented the functions of Education and quality management in MA Ar-Raihan Lattekko has been good enough even though there is still a better increase in the future.